Engaged Leadership Transforming through Future-Oriented Design Thinking (Management for Professionals,, 2018)
This professional book examines the concept of engaged leadership. Specifically, it focuses on the need for leaders in personal and professional realms, for-profit and non-profit, to understand the importance of engagement in order to achieve enhanced satisfaction and motivation among stakeholders (including employees, shareholders, investors, supporters, customers, suppliers, the community, competitors, family, and partners), and hence, an augmented level of designed thinking, which leads to increased innovation and on-going leadership development. Divided into three sections-engaged leadership development at the personal level, implementation at the organizational level, and manifestation in practice-this book provides professionals, practitioners and policy makers as well as students with the tools and skills to lead actively and conscientiously and help them understand the importance of creativity and compassion for development. Engaged leadership operates on the fundamental principle that leaders have to first and foremost perceive themselves as leaders, and then engage in design thinking, as they will need to develop strategies to reach, encourage, and positively appeal to these stakeholder groups. Leadership is neither limited to those holding formal managerial position, nor to any particular setting. Leaders can be found everywhere, in all layers of society. Leadership is only possible, however, if one dares to perceive and define oneself as a leader. And only when leadership is adopted as a reality within one's personal perception, can engaged leadership be applied. Featuring contributions from academics, scholars, and professionals from around the world, each providing cases, interactive questions and reflective notes, this book will be of interest to professionals, practitioners, policy makers, students and scholars interested in creative leadership, management, organizational behavior, and governance.